Famly Relationship: Family Reactions Face to a Member With Bipolar Disorder - Rosa Coser, Pâmela; Lima Both, Tatiana (Revista de Psicologia da IMED, 2013)
This research aimed to understand the family reactions face to member with bipolar disorder. The impact of the diagnosis for the family aimed to understand and identify the changes in family’s attitudes after receiving the news of the diagnosis and to identify the thoughts, feelings and behaviors face to familiar with bipolar disorder. This research was developed from the qualitative methodological approaches with relatives of the five patients with bipolar disorder that answered a semi structured interview. Through to analysis of the interviews aimed there is a little change in the diagnosis in relation to the feelings aroused in the family. However the thoughts become positive after the understanding the behavior by bipolar disorder. The acceptance of disease and treatment reflects to support feeling and realized family burden, either by suppression of negative feelings, or for the care expended by the instability of the patient.